ANALISIS KEMAMPUAN BERPIKIR KREATIF MAHASISWA PENDIDIKAN AKUNTANSI DALAM MEMBUAT INSTRUMEN TES HASIL BELAJAR SISWA MELALUI PEMBELAJARAN BERBASIS PROYEK - Purba Andi WIjaya; Nurhuda Nurhuda (Perspektif Pendidikan dan Keguruan, 2020)
This study aims to describe the creative thinking skills of accounting education students in making test instruments through project-based learning. This research is a descriptive study with data collection using documentation study techniques and tests conducted at the end of the learning program. The study was conducted on 81 accounting education students who were divided into 26 groups. The results of this study indicate the ability to think creatively in groups in either category, 16 groups (61.54%) are able to make questions with various categories. based on tests given to individual students, it showed 28 students (34.57%) the ability of students to think creatively in either category.